Bringing the Anglo-Scottish Border "Back in": Reassessing Cross-border Relations in the Context of Greater Scottish Autonomy. Issue 1 (2nd January 2018) - Shaw, Keith
ABSTRACT: This special issue of the Journal of Borderlands Studies "brings the Anglo-Scottish border back in" by drawing upon six of the contributions from an ESRC Seminar Series on the nature of the cross-border relationship between Scotland and its "closest cousins, " in Northern England. The seminars, which took place in 2014–2015, involved a range of contributors including academics, policy-makers and practitioners, with the academics drawn from a range of disciplines, including politics, cultural history, visual culture, economic geography, sociology, and planning. This introduction will examine the main characteristics of the Anglo–Scottish border and capture the nature of contemporary border change. It will then focus on the cross-border relationship between Scotland and the North of England before highlighting the key themes of the six articles contained in this special issue. It will conclude by examining how debates on the Anglo–Scottish border, and its borderlands, can be located within recent attempts to reconceptualize borders and bordering.